2010
DOI: 10.1002/masy.201000039
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ethylene methyl methacrylate and Ethylene butylacrylate Copolymers with Interactive Liquid Chromatography

Abstract: Copolymers of ethylene with methyl methacrylate (EMMA) and butyl acrylate (EBA), which are of different average chemical composition and block lengths according to NMR analysis, were analyzed by size exclusion chromatography (SEC), differential scanning calorimetry (DSC), Crystallization Analysis Fractionation (CRYS-TAF), and high performance liquid chromatography at high temperature (HT-HPLC). With CRYSTAF and DSC crystallizing fractions were detected only in some samples. HT-HPLC fractionated all the samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…GPEC is a kind of interaction liquid chromatography governed by the combination of entropic and enthalpic interactions between polymers and porous stationary phase in mobile phase solvents. [ 32–36 ] Thus, separation in GPEC depends simultaneously on polymer molecular weight and chemical composition. Although the enthalpic interaction during GPEC of polymers can be based on adsorption/desorption or precipitation/redissolution mode, precipitation/dissolution should be avoided because it might complicate polymer chromatography due to the low dissolution rate of polymers.…”
Section: Resultsmentioning
confidence: 99%
“…GPEC is a kind of interaction liquid chromatography governed by the combination of entropic and enthalpic interactions between polymers and porous stationary phase in mobile phase solvents. [ 32–36 ] Thus, separation in GPEC depends simultaneously on polymer molecular weight and chemical composition. Although the enthalpic interaction during GPEC of polymers can be based on adsorption/desorption or precipitation/redissolution mode, precipitation/dissolution should be avoided because it might complicate polymer chromatography due to the low dissolution rate of polymers.…”
Section: Resultsmentioning
confidence: 99%
“…Critical conditions were also determined for PS on silica gel using decalin and cyclohexanone at 1401C and applied to characterize ethylene-styrene block copolymers [88]. Albrecht and coworkers [56,[89][90][91][92] developed several chromatographic systems for the separation of EVA, ethylene-butylacrylate and EMA copolymers at 1401C, which ensure solubility of homopolymers as well as the copolymers. The units of the polar comonomers were adsorbed on silica gel from decalin or TCB, whereas the nonpolar units of methylene (i.e.…”
Section: Hplc Systems For the Separation Of Functionalized Olefin Copmentioning
confidence: 99%
“…Chitta et al . have shown that these admixtures falsified the values of the average chemical composition as determined by NMR spectroscopy 92. The conventional techniques such as CRYSTAF or DSC fail to detect these admixtures.…”
Section: Molecular Characterization Of Polyolefinsmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach to determine polymer end groups is using interactive polymer chromatography (IPC), in which retention in IPC is often dependent on the chemical composition, functionality, and molecular weight of the polymer. [12][13][14][15][16][17][18][19][20] More specifically, interaction gradient elution polymer chromatography (interactive GPEC). [17,[21][22][23] In interactive polymer LC, the retention is governed by the polymer interaction with the chemical groups of the chromatographic column's stationary phase, and the polarity and elution strength of the mobile phase.…”
Section: Introductionmentioning
confidence: 99%